2020
DOI: 10.1177/0731684420923043
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of contact-induced damage mechanisms in thick-walled composite cylinders

Abstract: In order to unravel the damage mechanisms occurring in composite-overwrapped pressure vessels (COPVs) subjected to crash conditions, a combined experimental-numerical study has been performed. For the purpose of generality and simplicity, quasi-static contacts on filament-wound cylinders are considered in this paper, as a precursor for geometrically complex impacts on COPVs. Rings with different wall thicknesses are tested to assess how failure mechanisms change when transitioning from thin-wall to thick-wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Hence, the first kink in the force-displacement curve (point A in Figure 3) is thought to be caused by the initiation of delamination. This theory is supported by earlier observations in, 21 in which thick-walled short composite cylinders were loaded in a similar manner as the pressure vessels here. It was shown that the first force drop in the force-displacement curve for the samples with a wall thickness close to that of pressure vessels was accompanied with a visible growth of delamination.…”
Section: Ct Imagessupporting
confidence: 90%
“…Hence, the first kink in the force-displacement curve (point A in Figure 3) is thought to be caused by the initiation of delamination. This theory is supported by earlier observations in, 21 in which thick-walled short composite cylinders were loaded in a similar manner as the pressure vessels here. It was shown that the first force drop in the force-displacement curve for the samples with a wall thickness close to that of pressure vessels was accompanied with a visible growth of delamination.…”
Section: Ct Imagessupporting
confidence: 90%
“…They offer lightweight crashworthy structures, unlike the metallic materials general use [1][2][3]. Extensive testing on different kinds of GFRP circular composite tube has demonstrated that composite materials can offer incredibly higher levels of specific energy absorption (SEA) and energy absorption capacity (Et) than their metallic co-equals [4][5][6]. Metal tubes assimilate energy through performing progressive plastic deformation, while the composite tubes absorb energy through progressive crushing mechanism showing more energy absorption compared to similar metallic tube [7].The dominant parameters in the energy absorption of composite structures consist of a type and volume fraction of thefiber and matrix, geometrical shapes, layering configuration andmanufacturing conditions [8,9].Energy absorbers can take various forms, such as circular tubes [10][11][12][13][14][15], square tubes [16,17], tapered and corrugated tubes [18][19][20][21], and foam-filled structures [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…13 Extensive testing on different kinds of GFRP circular composite tube has demonstrated that composite materials can offer incredibly higher levels of SEA and energy absorption capacity (Et) than their metallic co-equals. 46 Metal tubes assimilate energy through performing progressive plastic deformation, while the composite tubes absorb energy through progressive crushing mechanism showing more energy absorption compared to similar metallic tube. 7 The dominant parameters in the energy absorption of composite structures consist of a type and volume fraction of the fiber and matrix, geometrical shapes, layering configuration and manufacturing conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weerts et al, prelaminated a hydrogen storage tank and simulated delamination failure of the column section under quasistatic loading conditions by inserting zero-thickness cohesive elements. Interlaminar failure was usually the first visible mechanism for thick rings, whereas fiber fracture prevailed for thin rings [ 9 ]. Aleksandr Cherniaev et al, used the tiebreak contact algorithm to model interlaminar damage behavior and analyzed the effect of nonphysical parameters of the interlaminar material model on the prediction of compressive damage loads in damaged composite cylinders.…”
Section: Introductionmentioning
confidence: 99%